Cohen-Macaulay modules over the plane curve singularity of type T₃₆ - Drozd, Y.A.; Tovpyha, O. (Algebra and Discrete Mathematics, 2019)
For a wide class of Cohen–Macaulay modules over the local ring of the plane curve singularity of type T₃₆ we describe explicitly the corresponding matrix factorizations. The calculations are based on the technique of matrix problems, in particular, representations of bunches of chains.